Synthesis, activity and mechanism of alkoxy-, carbamato-, sulfonamido-, thioureido-, and ureido-derivatives of 2,4,5-trimethylpyridin-3-ol against inflammatory bowel disease - Chhabi Lal Chaudhary; Pallavi Gurung; Seoul Jang; Suhrid Banskota; Tae-Gyu Nam; Jung-Ae Kim; Byeong-Seon Jeong (Taylor & Francis Group, 2020)
Inflammatory bowel disease (IBD) is a chronic immuno-inflammation in gastrointestinal tract. We have evaluated the activity of the compounds to inhibit the adhesion of monocytes to colon epithelial cells is triggered by a pro-inflammatory cytokine, tumour necrosis factor (TNF)-α. The in vitro activity of the compounds, 13b (an ureido-derivative), 14c, 14j, 14k, 14n (thioureido-), 18c and 18d (sulfonamido-), was in correlation with in vivo anti-colitis activity revealed as significant recovery in body- and colon-weights and colon myeloperoxidase level, a biochemical marker of inflammation reflecting neutrophil infiltration. In vivo, TNBS-induced changes in the expression of inflammatory cytokines (TNF-α, IL-6, IL-1β, IL-10, and TGF-β), NLRP3 inflammasome components (NLRP-3, Caspase-1, and IL-18), and epithelial junction molecules (E-cadherin, claudin2/3, and ZO-1) were blocked and recovered by oral administration of the compounds (1 mg/kg). Compound 14n which showed the best efficacy can be a promising lead for orally available therapeutics for pathology of IBD.